INFLUENCE OF TRANSPORT FACTOR ON STOCKS IN LOGISTICS CHAINS OF RESOURCE BEHAVIOU - I. A. Lebedeva (Наука и техника, 2011)
The paper considers behaviour of material flows at stages of complicated  logistic industrial and transport systems. Key parameters of logistic delivery schemes are analyzed in the paper. The paper estimates an influence of a time parameter on the level of transport and logistics costs and, as a consequence, on  a final finished product.While determining a stock level it is necessary to know not only an intensity of material resource consumption by manufacturing process  for a concrete period of time, but also a probability of non-observance of   transport service terms and cost of stock storage. Stocks of mass cargoes are basically formed at first stages of industrial and transport system and cost of their storage is relatively insignificant. However deficit presence of the given resources influences on functioning of all subsequent interrelated stages of the industrial and transport system.Thus, a risk of deficit occurrence of the given resources can be probably reduced by creating a high stock rate. There is a processing of hi-tech component items (or half-finished products) at last stages of the industrial and transport system. Expenses on storage of such resources  are usually high and possibility of their substitution by analogous ones is insignificant. At last stages a mobilization of facilities for provision of on-time delivery is more profitable that allows to save on stock arrangement.